Differential responses on energy metabolic pathway reprogramming between genotoxic and non-genotoxic hepatocarcinogens in rat liver cells - Ito, Yuko (J Toxicol Pathol, 2019)
To clarify difference in the responses on the reprogramming of metabolism toward carcinogenesis between genotoxic and non-genotoxic hepatocarcinogens in the liver, rats were repeatedly administered genotoxic hepatocarcinogens (N-nitrosodiethylamine, aflatoxin B(1), N-nitrosopyrrolidine, or carbadox) or non-genotoxic hepatocarcinogens (carbon tetrachloride, thioacetamide, or methapyrilene hydrochloride) for 28, 84, or 90 days. Non-genotoxic hepatocarcinogens revealed transcript expression changes suggestive of suppressed mitochondrial oxidative phosphorylation (OXPHOS) after 28 days and increased glutathione S-transferase placental form-positive (GST-P(+)) foci downregulating adenosine triphosphate (ATP) synthase subunit beta, mitochondrial precursor (ATPB), compared with genotoxic hepatocarcinogens after 84 or 90 days, suggesting that non-genotoxic hepatocarcinogens are prone to suppress OXPHOS from the early stage of treatment, which is in contrast to genotoxic hepatocarcinogens. Both genotoxic and non-genotoxic hepatocarcinogens upregulated glycolytic enzyme genes and increased cellular membrane solute carrier family 2, facilitated glucose transporter member 1 (GLUT1) expression in GST-P(+) foci for up to 90 days, suggesting induction of a metabolic shift from OXPHOS to glycolysis at early hepatocarcinogenesis by hepatocarcinogens unrelated to genotoxic potential. Non-genotoxic hepatocarcinogens increased c-MYC(+) cells after 28 days and downregulated Tp53 after 84 or 90 days, suggesting a commitment to enhanced metabolic shift and cell proliferation. Genotoxic hepatocarcinogens also enhanced c-MYC activation-related metabolic shift until 84 or 90 days. In addition, both genotoxic and non-genotoxic hepatocarcinogens upregulated glutaminolysis-related Slc1a5 or Gls, or both, after 28 days and induced liver cell foci immunoreactive for neutral amino acid transporter B(0) (SLC1A5) in the subpopulation of GST-P(+) foci after 84 or 90 days, suggesting glutaminolysis-mediated facilitation of cell proliferation toward hepatocarcinogenesis. These results suggest differential responses between genotoxic and non-genotoxic hepatocarcinogens on reprogramming of energy metabolic pathways toward carcinogenesis in liver cells from the early stage of hepatocarcinogen treatment.